2012
DOI: 10.3928/15428877-20120531-01
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc and Retinal Nerve Fiber Layer Parameters of Eyes With Keratoconus

Abstract: RNFL thickness between patients with keratoconus and healthy subjects seems to be more comparable than ONH parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
4
12
0
2
Order By: Relevance
“…In the present study, the mean RNFL thickness measurements for the nasal quadrants were almost identical in the two groups. This finding is in accordance with previous studies 3,35 which have reported less than 3 µm nasal quadrant RNFL thickness differences between individuals with keratoconus and healthy controls.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In the present study, the mean RNFL thickness measurements for the nasal quadrants were almost identical in the two groups. This finding is in accordance with previous studies 3,35 which have reported less than 3 µm nasal quadrant RNFL thickness differences between individuals with keratoconus and healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…The mean RNFL measurements were marginally higher (1 µm -13 µm) in the control group for all quadrants with the exception of only the nasal quadrant in the left eye where the same value (78 µm) was noted in the two groups. This finding is consistent with reports from previous studies, 3,35 which also noted lower quadrant-specific mean RNFL thickness measurements in individuals with keratoconus when compared with healthy controls. For the superior quadrant, Bayhan et al 35 reported a 13.6 µm statistically significant (p = 0.045) RNFL thickness difference between the keratoconus and control groups which is almost identical to the difference (13 µm, p ≤ 0.015) noted for the superior quadrant of both eyes in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations